2018
DOI: 10.1186/s41100-018-0167-6
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Japanese version of the 5-D itch scale for rating pruritus experienced by patients undergoing hemodialysis

Abstract: Background: Pruritus in patients undergoing hemodialysis reduces quality of life via insomnia and depression, and negatively affects prognosis. For diagnosing pruritus, selecting therapeutic strategies, and determining therapeutic outcomes, methods are needed for objectively quantifying the degree of itchiness. In 2015, the Japanese version of the 5-D itch scale (5D-J), originally developed in the USA in 2010, was developed as a simple self-administered questionnaire; it evaluated the degree of itchiness based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…However, the majority (86.3%) reported that their pruritus was mild. Our findings differed from previous studies which reported prevalence rates of mild pruritus as 48.8% in Japan [ 35 ], 22.2% in Egypt [ 36 ], and 41.7% in Saudi Arabia [ 37 ]. In our setting, only high-flux dialyzers were used, and studies have shown that high-flux dialyzers efficiently remove average-sized molecules associated with the aggravation of pruritus better than low-flux dialyzers [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, the majority (86.3%) reported that their pruritus was mild. Our findings differed from previous studies which reported prevalence rates of mild pruritus as 48.8% in Japan [ 35 ], 22.2% in Egypt [ 36 ], and 41.7% in Saudi Arabia [ 37 ]. In our setting, only high-flux dialyzers were used, and studies have shown that high-flux dialyzers efficiently remove average-sized molecules associated with the aggravation of pruritus better than low-flux dialyzers [ 38 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The VAS score was almost comparable with the previous studies, 5,13,27 whereas 5D-J showed that our patients appeared to have the same or higher total score and more frequent complaints of pruritus on the abdomen than patients with HD. 25 Our results revealed that higher serum TARC level was significantly correlated with both VAS and 5D-J score and was an independent predictor of them even after adjusting for confounding factors. Although eosinophil count positively correlated with both VAS and 5D-J scores, multivariate analysis did not show a significant association with them.…”
Section: Discussionmentioning
confidence: 49%
“…23 In addition, the Japanese version of the 5-D itch scale (5D-J) was used for evaluating pruritus-related QOL. 24,25 The 5D-J comprises five components (degree, duration, direction, disability and distribution), and its total scores range from 5 to 25, with higher scores indicating worse pruritus-related QOL. In the component of distribution, all the body sites where pruritus has been present over 2 weeks were recorded for each participant, including the head/scalp, face, chest, abdomen, back, buttocks, thighs, lower legs, tops of feet/toes, soles, palms, tops of hands/fingers, forearms, upper arms, points of contact with clothing or groin.…”
Section: Methodsmentioning
confidence: 99%
“…The original version of the scale reported the internal consistency as 0.73 [ 9 ]. The Japanese version of the scale did not report the internal consistency [ 23 ]. In line with Urdu (ICC= 0.91), Arabic (ICC=0.85), and the original version (ICC=0.96), the Persian version of the 5-D scale showed excellent test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The Indonesian version had a strong correlation with the dermatology life quality index and the VAS [ 20 ]. The Japanese version of the scale showed strong correlation with vas ( r =0.70), daytime itchiness ( r =0.64), and nighttime itchiness ( r =0.63) [ 23 ]. Other versions of the scale did not evaluate the correlation of the scale with other related instruments.…”
Section: Discussionmentioning
confidence: 99%